Alexithymia Predicts Carotid Atherosclerosis, Vascular Events, and All-Cause Mortality in Human Immunodeficiency Virus-Infected Patients: An Italian Multisite Prospective Cohort Study. (27th July 2019) - Vadini, Francesco; Sozio, Federica; Madeddu, Giordano; De Socio, Giuseppe; Maggi, Paolo; Nunnari, Giuseppe; Vichi, Francesca; Di Stefano, Paola; Tracanna, Elisa; Polilli, Ennio; Sciacca, Antonina; Zizi, Bernardetta; et al.
Abstract: Background: Psychological factors (PFs) are known predictors of cardiovascular disease (CVD) in many clinical settings, but data are lacking for human immunodeficiency virus (HIV) infection. We carried out a prospective study to evaluate (1) psychological predictors of preclinical and clinical vascular disease and (2) all-cause mortality (ACM) in HIV patients. Methods: We conducted a cross-sectional analysis of baseline data to evaluate the predictors of carotid plaques (CPs) and a prospective analysis to explore predictors of vascular events (VEs) and ACM over 10 years. Human immunodeficiency virus patients monitored at the Infectious Disease Units of 6 Italian regions were consecutively enrolled. Traditional CVD risk factors, PFs (depressive symptoms, alexithymia, distress personality), and CPs were investigated. Vascular events and ACM after enrollment were censored at March 2018. Results: A multicenter cohort of 712 HIV-positive patients (75.3% males, aged 46.1 ± 10.1 years) was recruited. One hundred seventy-five (31.6%) patients had CPs at baseline. At the cross-sectional analysis, alexithymia was independently associated with CPs (odds ratio, 4.93; 95% confidence interval [CI], 2.90–8.50; P < .001), after adjustment for sociodemographic, clinical, and psychological variables. After an average follow-up of 4.4 ± 2.4 years, 54 (7.6%) patients developed a VE, whereas 41 (5.68%) died. Age, current smoking, hypertension, and alexithymia (hazard ratio [HR], 3.66; 95% CI, 1.80–7.44; P < .001) were independent predictors of VE. Likewise, alexithymia was an independent predictor of ACM (HR, 3.93; 95% CI, 1.65–9.0; P = .002), regardless of other clinical predictors. Conclusions: The present results validate our previous monocentric finding. Alexithymia may be an additional tool for the multifactorial assessment of cardiovascular risk in HIV.